2017
DOI: 10.1186/s13568-017-0380-7
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and inactivation of Shiga toxins by nitrogen gas plasma

Abstract: Shiga toxin (Stx)-producing Escherichia coli (STEC) leads to food poisoning by causing hemorrhagic colitis and hemolytic uremic syndrome. Some STEC produce Shiga toxin 1 (Stx1) and/or Shiga toxin 2 (Stx2), a relatively stable protein toxin, necessitating the development of an efficient inactivation method. Here we applied a nitrogen gas plasma apparatus to the inactivation of Stx. Samples of Stx1 and Stx2 were treated with a nitrogen gas plasma generated by a plasma device using a short high-voltage pulse appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Differences where ** p < 0.01 versus control (0 min) were considered significant. ( a ) and ( b ) are cited from Sakudo et al [57] with permission from Elsevier, while ( c ) and ( d ) are cited from Sakudo et al [74] under the terms of the Creative Commons Attribution 4.0 International license.…”
Section: Figurementioning
confidence: 99%
“…Differences where ** p < 0.01 versus control (0 min) were considered significant. ( a ) and ( b ) are cited from Sakudo et al [57] with permission from Elsevier, while ( c ) and ( d ) are cited from Sakudo et al [74] under the terms of the Creative Commons Attribution 4.0 International license.…”
Section: Figurementioning
confidence: 99%
“…For example, a review article written by Kutasi et al [ 44 ] highlighted the challenges and approaches towards inactivating aflatoxins using UV radiation and pulsed light treatment, ammoniation, ozonation, and gas plasma. Sakudo et al demonstrated the effectiveness of nitrogen gas plasma against aflatoxin B 1 [ 25 ] and Shiga toxins [ 26 ]. Our findings build upon these studies, showcasing the broader applicability and effectiveness of APDBD plasma against a range of foodborne toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these considerations, we have developed an advanced technique designed to efficiently degrade foodborne toxins whilst preserving the intrinsic characteristics of the food during the decontamination phase. Our previous studies revealed that nitrogen gas plasma treatment can degrade aflatoxin B 1 [ 25 ] and Shiga toxins [ 26 ]. In addition, a broad range of degradation activity against various toxins by plasma has been reported by other research groups [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma is a novel advanced disinfection/sterilization system that can simultaneously inactivate pathogens, viruses, and their associated toxins. [22,92,97,98] In the late 1960s, plasma was beginning applied to decontaminate surfaces, and in some aspects demonstrated to be more effective than conventional sterilization. [99] What's more, the treatment of plasma exerts relatively little impact on the structural integrity of sterilized samples.…”
Section: Sterilizationmentioning
confidence: 99%